Identification of Antimalarial Inhibitors Using Late-Stage Gametocytes in a Phenotypic Live/Dead Assay. (January 2019) - Spicer, Timothy P.; Gardiner, Donald L.; Schoenen, Frank J.; Roy, Sudeshna; Griffin, Patrick R.; Chase, Peter; Scampavia, Louis; Hodder, Peter; Trenholme, Katharine R.
Malaria remains a major cause of morbidity and mortality worldwide with 3.3 billion people at risk of contracting malaria and an estimated 450, 000 deaths each year. While tools to reduce the infection prevalence to low levels are currently under development, additional efforts will be required to interrupt transmission. Transmission between human host and vector by the malaria parasite involves gametogenesis in the host and uptake of gametocytes by the mosquito vector. This stage is a bottleneck for reproduction of the parasite, making it a target for small-molecule drug discovery. Targeting this stage, we used whole Plasmodium falciparum gametocytes from in vitro culture and implemented them into 1536-well plates to create a live/dead phenotypic antigametocyte assay. Using specialized equipment and upon further validation, we screened 150, 000 compounds from the NIH repository currently housed at Scripps Florida. We identified 100 primary screening hits that were tested for concentration response. Additional follow-up studies to determine specificity, potency, and increased efficacy of the antigametocyte candidate compounds resulted in a starting point for initial medicinal chemistry intervention. From this, 13 chemical analogs were subsequently tested as de novo powders, which confirmed original activity from the initial analysis and now provide a point of future engagement.